The Effect of Workplace Bullying and Job Satisfaction on Turnover Intention of Employee - Nurdiana, Ilfi; Elyatin, Leny; Safitri, Rini (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2021)
A good environment can be formed through relationships between employees. The relationship between these employees will later have an effect on employee performance, it can be concluded that the relationship between employees is very important to be in the scope of a company organization. Workplace bullying is an act that should not exist in a company or organization. However, it cannot be denied that workplace bullying is now a phenomenon and a problemÂ for companies. The existence of workplace bullying against employees will cause an employee to feel threatened and if there is constant eating it will cause the employee to have the intention to change jobs (turnover intention ) and looking for a new workplace out there, besides that workplace bullying also causes dissatisfaction dan decrease employee performance which will also disrupted company operations. This research uses quantitative research. Data analysis in this study used the PLS (Partial Least Square) analysis test. The population in this study were employees of the Amaris Hotel Surabaya and data collected using a questionnaire and the sample used in this study was a saturated sampling method. The results of this study indicate that workplace bullying has a positive and significant effect on turnover intention. And job satisfaction cannot moderate the relationship workplace bullying to turnover intention.